Evolution of SCADA architecture: from centralized models to cloud-based solutions - Іevtushenko, V. I.; Sotnik, S. V. (ХНУРЕ, 2026)
The work is devoted to the study of the transformation of SCADA system architectures in the context of the digital transformation of industrial enterprises. The historical prerequisites for the transition from centralized on-premise deployments to distributed and cloud oriented solutions are identified. The role of edge computing as an intermediate layer that ensures fault tolerance and operational autonomy of remote facilities is characterized. The specifics of web oriented human-machine interfaces based on HTML5, WebSocket and RESTful API technologies are outlined. It is shown that the hybrid architecture, which combines local real-time processing with cloud-based analytics and long-term data storage, represents the most balanced approach for modern industrial automation within the Industry 4.0 paradigm. Робота присвячена вивченню трансформації архітектур SCADA-систем у контексті цифрової трансформації промислових підприємств. Виокремлено історичні передумови переходу від централізованих локальних рішень до розподілених та орієнтованих на хмарні технології. Охарактеризовано роль edge-обчислень як проміжного рівня, що забезпечує відмовостійкість та операційну автономність віддалених об'єктів. Наведено особливості веб-орієнтованих інтерфейсів «людина-машина» на базі технологій HTML5, WebSocket та RESTful API. Показано, що гібридна архітектура, яка поєднує локальну обробку даних у режимі реального часу з хмарною аналітикою та довгостроковим зберіганням даних, є найзбалансованішим підходом для сучасної промислової автоматизації в рамках парадигми Industry 4.0.
Еволюція архітектури SCADA: від централізованих моделей до хмарно-орієнтованих рішень
Keywords: SCADA; cloud technologies; web-based systems; edge computing; промислова автоматизація; microservice architecture; мікросервісна архітектура